Shariah Supervisory Boards conception of accountability and competency: an ethnographic study of Bank Muamalat Malaysia Berhad - Mohamad Yunus, Mohd Hadli Shah; Mustafa, Hasri (INSInet Publications, 2016)
Background: This study describes the rationales for the study and the importance of proper recognition of the accountability conception and competence among Shariah Supervisory Boards (SSBs) in the Islamic Financial Institution (IFI). Objective: This research examines the relationship between the level of accountability conception and competency of the members of Shariah Supervisory Boards (SSBs) of Islamic Financial Institution (IFI) on their main duties and responsibilities. It also examines the IFI interpretation and evaluate whether in accordance with Shariah principles; and the epistemological conception of accountability amongst SSB members in the IFI and examine the association between the level of competency and accountability of SSB. Methodology: In this study, the qualitative research method was applied and ethnographic research approach was employed so as to understand the social context on the accountability and level of competency amongst SSB. Results: The findings of this study primarily revealed that the SSB members dealing precisely with regards to the Shariah compliance comprehension in association with IFI interpretation and accountability conception. Moreover, this study also found that the epistemological conception of accountability emphasizes on the subjection, transparency, independence, confidentiality, faith and justice shows the relationship between self and statutory regulations positively influenced by Islamic business ethic. Hence, the association level of competency and accountability has a significant influenced in supporting SSB supervising the IFI accordingly. Conclusion: This research can make a significant contribution to the IFI in providing full range of knowledge and skills to determine the problems or issues pertaining to the concept of accountability among SSB. Results of the study could be used to improve existing services and formulate strategic decisions in order to achieve competitive advantage, designing and implementing suitable remedial measures.